Aerial competition, digital sports and 4ir technology: a cross-sectional survey during the COVID-19 pandemic - Zhang, X.; Wu, F. (Design Engineering, 2021)
Due to the COVID-19 outbreak, all global sports events have been suspended. In order to better promote the in-depth integration of sports events and digitalization, this study aims to explore airborne sports competitions, which are based on Internet technology and use digital media to achieve Digitization of sports competitions. In order to evaluate the effects of digital sports events, from September to December 2020, the research tracked the World Health Qigong and Global Taijiquan competitions (digital space sports competitions) held by China. It also interviewed 8 international referees and investigated 64 National level referees, 228 national level one and level two referees, and 592 athletes participating in digital sports competitions to evaluate the feasibility of digital sports events. The research results show that the holding of Health Qigong and Taijiquan competitions provides a new path for the development of digital sports events, through which users of the competition can communicate in digital media to achieve the spatial and physical interaction of the competition in the air. The effect, especially the pandemic like COVID-19, not only greatly meets citizens` exercise needs, but also relieves the various emotions and psychological worries caused by citizens` home isolation, and is an effective response to the fight against COVID-19. The holding of this event provides a useful reference for the in-depth integration of digitalization and sports competitions.